Guadalupe, Honduras. Kulturelle Interaktion und vorspanische Siedlungsgeschichte im Nordosten von Honduras. Die Arbeiten der Jahre 2016 und 2017 - Reindel, Markus; Fux, Peter; Fecher, Franziska (e-Forschungsberichte des DAI, 2017)
Starting in 2016, archaeological investigations were carried out in Guadalupe, an extended postclassic (1000–1521 AD) settlement on the Northeast Coast of Honduras. Northeast Honduras is a little studied region in the interaction sphere of Mesoamerica and Southern Central America. Archaeological excavations in Guadalupe were realized with the aim of enlarging the data base about the settlement history and cultural developments of that region. The unexpected abundance of artifacts will enable us to refine the existing typochronologies of artifacts and will give us new insights into the interregional cultural relations of the late pre-Hispanic period.